2015
DOI: 10.1007/s11676-015-0053-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage and sequestration rate assessment and allometric model development in young teak plantations of tropical moist deciduous forest, India

Abstract: Carbon (C) sequestration through plantations is one of the important mitigation measures for rising levels of carbon dioxide and other greenhouse gases in the atmosphere. This study aimed to assess C stocks and their sequestration rate, and to develop allometric models for estimation of C stocking in age-series young teak (Tectona grandis) plantations (1, 5, 11, 18, 24 and 30 years) by using biomass and productivity estimation and regression, respectively. These plantations were raised in tropical moist decidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…For example, an assessment of carbon stocks by Jah (2015) in young (1, 5, 11 years old) Tectona grandis plantations with stand densities of 1183, 1728 and 376 trees per hectare respectively, growing under similar environmental conditions as the present study showed that 1.6, 15.8, and 35.4 Mg ha -1 was stored in the 1-year, 5-year, 11-year-old Tectona grandis standsrespectively. By comparison, it is evident that the 4-year-old Tectona grandis stand in our study stores more carbon than the 5-year-old Tectona grandis stand studied by Jha (2015), notwithstanding that the stand density in the Jha (2015) study was almost twice higher (1728 trees per ha) than in the current study (911 tree per ha). This suggests that the trees at the project sites potentially can sequester significant quantities of carbon and gain carbon credits in the future.…”
Section: Benefits and Ecosystem Services From The Restored Forestscontrasting
confidence: 68%
“…For example, an assessment of carbon stocks by Jah (2015) in young (1, 5, 11 years old) Tectona grandis plantations with stand densities of 1183, 1728 and 376 trees per hectare respectively, growing under similar environmental conditions as the present study showed that 1.6, 15.8, and 35.4 Mg ha -1 was stored in the 1-year, 5-year, 11-year-old Tectona grandis standsrespectively. By comparison, it is evident that the 4-year-old Tectona grandis stand in our study stores more carbon than the 5-year-old Tectona grandis stand studied by Jha (2015), notwithstanding that the stand density in the Jha (2015) study was almost twice higher (1728 trees per ha) than in the current study (911 tree per ha). This suggests that the trees at the project sites potentially can sequester significant quantities of carbon and gain carbon credits in the future.…”
Section: Benefits and Ecosystem Services From The Restored Forestscontrasting
confidence: 68%
“…However, higher RSR values were also reported for Juniperus procera (42%) and Acacia abyssinica (54%) from northern Ethiopia [52]. Such variations indicate that the root-shoot ratio might vary depending on tree species, tree size, tree age, agroecology, soil conditions, and water stress level [18,23,24]. Thus, it is important to be cautious when using RSR values to estimate the belowground biomass, particularly when there is no available species-specific RSR values for the study tree species [24].…”
Section: Discussionmentioning
confidence: 92%
“…Carbon stock estimation was done using biomass estimated above and Carbon conversion factor (Gower et al, 2001;Nowak and Crane, 2002;Terakunpisut et al, 2007;Jha, 2015).…”
Section: Carbon Stock Estimationmentioning
confidence: 99%
“…Further, Magnussen and Reed (2004) have proposed to take 0.475 as a fraction of biomass to estimate Carbon in any vegetation. Nevertheless, instead of taking empirical factor, it is always good to take species and site specific factor (Jha, 2015) to have accurate estimation since universal factor is prone to over-estimation or under-estimation in the specific case. Since there was no factor available for the study area and concentration varied in different plant parts (Table 1), an average Carbon concentration value (45.56%) of roots of poplar plantations growing in different climates was used as conversion factor in this study.…”
Section: Carbon Stock Estimationmentioning
confidence: 99%